Persepsi pengunjung terhadap Muzium Warisan Baba dan Nyonya Melaka - Zawiah, Binti Samsudin. (Universiti Malaysia Sarawak (UNIMAS), 2008)
The purpose of this research is to identify and visitors ' perceptions towards The Baba and Nyonya Heritage Museum in terms ofexhibition, facilities. information provided, environment, communication as well as the purpose of their visit. The researcher would IiJce 10 find out 'why ' the museum only receives a few visitors and also find out the level of awareness among society ofBaba Nyonya culture and the museum itself Besides that, the researcher would like to promote Baba Nyonya culture and help the museum to increase their productivity in order to attract more visitors.